Integration of Soft Skills Strategy in Teaching Akidah Akhlak at State Madrasah Aliyah - Satir, Muhammad; Akidah, Sri; Hasbullah, Hasbullah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study investigates the integration of soft-skill strategies in teaching Akidah Akhlak at MAN Kota Sorong, driven by the issue of limited awareness between teachers and students. The research aims to explore how interpersonal, intrapersonal, and effective communication skills are embedded within the teaching process, the role of teachers as facilitators and learning managers, and the forms of evaluation and constructive feedback used. Employing a qualitative phenomenological approach, the study involved 14 participants—12 students (6 males and six females) selected from 300 eleventh-grade students based on character diversity and family background, and 2 Akidah Akhlak teachers. Data were collected through in-depth interviews and classroom observations and were then analysed thematically to reveal the lived experiences and meanings participants perceived. Findings indicate that most students recognized the partial integration of soft skills through thematic and cooperative learning; yet, several admitted that such practices were rarely emphasized or explicitly connected to moral instruction. Teachers reported limited mastery and consistency in applying soft-skill-based approaches due to curriculum rigidity and inadequate training. Despite these challenges, both teachers and students agreed that integrating soft skills—such as empathy, communication, and self-control—greatly enhances moral awareness and character formation. The study concludes that embedding soft skills into Akidah Akhlak instruction is essential for addressing pedagogical and behavioural challenges. It recommends systematic teacher training and technology-based learning designs to strengthen students’ moral competence and adaptive interpersonal behaviour.